Sorption of metaldehyde using granular activated carbon - Salvestrini, S.; Vanore, P.; Bogush, A.; Mayadevi, S.; Campos, L. C. (Journal of Water Reuse and Desalination, 2017)
In this work, the ability of granular activated carbon (GAC) to sorb metaldehyde was evaluated. The kinetic data could be described by an intra-particle diffusion model, which indicated that the porosity of the sorbent strongly influenced the rate of sorption. The analysis of the equilibrium sorption data revealed that ionic strength and temperature did not play any significant role in the metaldehyde uptake. The sorption isotherms were successfully predicted by the Freundlich model. The GAC used in this paper exhibited a higher affinity and sorption capacity for metaldehyde with respect to other GACs studied in previous works, probably as a result of its higher specific surface area and high point of zero charge.
Keywords: Degradation; Diffusion-controlled Sorption; Environmental Pollution; Granular Activated Carbon; Metaldehyde; Sorption Adsorption